Same-day mastectomy and axillary lymph node dissection is safe for most patients with breast cancer - Tamminen Anselm; Meretoja Tuomo; Koskivuo Ilkka (WILEY, 2022)
Background and Objective: The aim of this study was to evaluate the safety of same-day mastectomy, with or without a sentinel node biopsy (SNB) and/or axillary lymph node dissection (ALND).
Methods: In this retrospective study, we reviewed 913 consecutive women who underwent a simple mastectomy for breast cancer between the years 2014 and 2019 and were treated either with same-day surgery (SDS) or an overnight stay (OS) regime. We reviewed all surgical complications, any unplanned return to care (RTC) and the rehospitalization rate for 30 postoperative days.
Results: A total of 259 patients (28%) were treated with SDS and 654 patients (72%) with an OS regime. There was no difference in RTC (odds ratio: 0.79 [95% confidence interval: 0.53-1.18], p = 0.26) or any major complications between the groups. None of the investigated subgroups, such as patients with previous neoadjuvant therapy, diabetes, obesity (up to a body mass index of 40 kg/m(2)), the American Society of Anaesthesiologist Class of 3, or elderly patients aged 75-84 years, showed an increased complication rate when treated with the SDS regime.
Conclusion: A same-day simple mastectomy is safe with SNB and/or ALND. It can be performed safely for most patients with stable co-morbidities.